बारेला : जनजातीय जीवन एवं संस्कृति - Tawar, Gulnaz (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2007)
The book emphasized on the livelihood and cultural development of Barela tribes in Madhya Pradesh region.
Barela: Janjaatiya Jeevan Evam Sanskriti
Keywords: Folk Culture; Hindi